ASCERTAINMENT OF DYNAMIC CHARACTERISTICS OF THE INDUSTRIAL FACILITIES BY MEANS OF STOCHASTIC ACTIONS - Ya. А. Gusentsova; Ye. S. Gusentsova; A. A. Kovalenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents comparison of different methods for identifying the dynamic characteristics of objects associated with thermal energy generation or the medium cooling in the cooling systems of internal-combustion engines. Reaction identification to the reference exposure is considered, videlicet – stepwise, impulse and harmonic. The study shows that on a number of occasions for the type of objects being involved their application is unacceptable. In those instances it is expediential to apply statistical characteristics of the input and output signals, i. a. to employ the data of so-called passive experiment. In which case the task is divisible into two stages – determination of statistical characteristics of the variates at the ins and outs of the object and calculation of the dynamic characteristics based on them. The statistical characteristics of the variates at the input and output are obtained through time averaging of values of the variates dependent on the ordinate of the processes. Inasmuch as stochastic processes occurring in the objects under examination possess ergodic property, their averaged values are constant. All the data required for calculating characteristics of the linear systems appears in their correlative functions. Heat generating objects as well as the cooling systems of internal-combustion engines are the objects fed back by the regulator. Therefore, in this instance cross-correlated functions are employed for determining their dynamic characteristics. The suggested random-input analytical method for dynamic characteristics constitutes a good match with the results of active experiments reported in a variety of sources. This allows recommending the random signals estimation method of dynamic characteristics for the involved type of objects.